(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
This article examines some of the main effects of the implementation of anti-maras policies in El Salvador. In this context, it will highlight the complex transformations that have taken place within the gangs and, in particular, within the criminal organisation of the Mara Salvatrucha: the consolidation and expansion of territorial control and the professionalization of the exercise of violence, with a focus on the phenomenon of desaparición, a true national humanitarian emergency.